Privacy, boundaries and smart homes for health: An ethnographic study. (March 2018) - Burrows, Alison; Coyle, David; Gooberman-Hill, Rachael
Abstract: This article explores how people negotiate borders and boundaries within the home, in the context of health and the introduction of new technologies. We draw on an ethnographic study involving a socially diverse group of people, which included people with experience of telecare or smart home energy systems. Participants engaged in various strategies to regulate the borders of their home, even though new technologies have begun to change the nature of these borders. Participants managed health conditions but also their use of technology through boundary work that permitted devices to be more or less visible and integrated within the home. Findings highlight that if smart healthcare technologies are to be accepted in the home then there is a need for mechanisms that allow people to control the interpretation of data and flow of information generated about them and their households. Highlights: Smart home technology has been heralded as a new way of managing health. Research needs to explore acceptability and implications of smart home technology. This study examined people's use of homes in the context of health and technology. Participants used various strategies to regulate borders in their homes. Smart home technologies should allow personal control of data and information flow.